Establishing a standard definition for child overweight and obesity worldwide: international survey. Issue 7244 (6th May 2000) - Cole, Tim J; Bellizzi, Mary C; Flegal, Katherine M; Dietz, William H
Abstract: Objective: To develop an internationally acceptable definition of child overweight and obesity, specifying the measurement, the reference population, and the age and sex specific cut off points. Design: International survey of six large nationally representative cross sectional growth studies. Setting: Brazil, Great Britain, Hong Kong, the Netherlands, Singapore, and the United States Subjects: 97 876 males and 94 851 females from birth to 25 years of age Main outcome measure: Body mass index (weight/height2). Results: For each of the surveys, centile curves were drawn that at age 18 years passed through the widely used cut off points of 25 and 30 kg/m2 for adult overweight and obesity. The resulting curves were averaged to provide age and sex specific cut off points from 2-18 years. Conclusions: The proposed cut off points, which are less arbitrary and more internationally based than current alternatives, should help to provide internationally comparable prevalence rates of overweight and obesity in children.